Avaliação do mecanismo de ação in vitro e dos efeitos biológicos in vivo induzido pelas dibenzilidenoacetonas A3K2A1 e A3K2A3 em Trypanosoma cruzi - Bidóia, Danielle Lazarin (2015)
Despite ongoing efforts, the available treatments for patients with Chagas' disease are still unsatisfactory, especially in the chronic phase of the disease. Our previous study reported the strong trypanocidal activity of the dibenzylideneacetones A3K2A1 and A3K2A3 against Trypanosoma cruzi. In the present study, we investigated the mechanisms of action of these compounds that are involved in parasite death. We showed that A3K2A1 and A3K2A3 induced oxidative stress in the three parasitic forms, especially trypomastigotes, reflected by an increase in oxidant species production and reduction of the endogenous antioxidant system. This oxidative imbalance culminated in damage in essential cell structures of T. cruzi, reflected by lipid peroxidation and DNA fragmentation. Consequently, A3K2A1 and A3K2A3 induced vital alterations in T. cruzi, leading to parasite death by different pathway, including apoptosis and autophagy. Moreover, the in vivo data support new preclinical studies with different therapeutic protocols and using modified release systems, in order to achieve better results for the development of new chemotherapeutic agents against T. cruzi.